Efektifitas Model Pembelajaran Artikulasi dan Style Belajar Visual pada Pembelajaran Maharatul Kalam di MTs Satu Atap Al-Hidayah Batu - Huri, Adam; Mubaligh, Ahmad; Fitriani, Laily (Shaut al Arabiyyah, 2025)
The purpose of this study is to measure the effectiveness of using an articulation learning model combined with a visual learning style in teaching Mahārat al-Kalām skills by comparing a control class and an experimental class. This study uses a quasi-experimental method with test instruments, and involves two classes, namely class 8 A and class 8 B, as subjects. Class 8A was the experimental class, meaning that it received treatment in the form of articulation learning and visual learning styles, while class 8B was the control class, meaning that it was taught using conventional procedures. Data were obtained through observation, testing, and interviews, then analyzed using an independent sample t-test. Based on the analysis of the information, the results show that the use of the articulation education model combined with visual learning styles in Mahārat al-Kalām skills education is effective in improving students' dialogue skills. This is based on the test results, which show a t-test value of 4.440, indicating a significant effect. Not only that, the average score for small group presentations on the topics of arriyādhah, al-mihnah, and al-mardhā fī al-mustasyfā in the control class (61.04) was lower than that of the experimental class (77.00). Therefore, it can be concluded that the articulation education model is more efficient than the method.